Possibilities of improving students’ reading literacy - Халитова, Ильдана; Шайхелисламов, Раис (Pedagogy and Psychology, 2022)
This article analyzes materials from the Commonwealth Economic and Development Organization (OECD) related to the Program for International Student Assessment (PISA) for 15-year-olds. The purpose of the analysis is to identify the reading literacy skills that students need to develop. The reasoning in this article begins with an analysis of the definition of reading literacy itself, which already provides some list of skills and abilities. Further examination of documentation and research in the area in question showed that the list of skills is ambiguous. Thus, this article attempts to provide some possible clarity, as skills are the result of learning. Consequently, a clear idea of the skills that need to be formed in the classroom at school, consistently develop them in subsequent grades. In this article the authors take the position that the value of reading literacy skills is, first of all, determined by their life necessity related to the need of already mature 15-year-olds to engage in economic and social relationships. Second, the results of the PISA study allow participating countries to implement reforms aimed at improving the quality of the educational system. Third, PISA results are directly related to the competitiveness rankings of OECD countries, in which non-OECD member countries also participate. The proposed article is part of a project related to research on the skills teachers need to be effective in preparing children for life, shaping their functional literacy. It may therefore be of interest to functional literacy researchers, school teachers, and teacher educators.